A comprehensive investigation on electrical characterization and ionic transport properties of cellulose derivative from kenaf fibre-based biopolymer electrolytes - Rani, Mohd Saiful Asmal; Ahmad, Azizan; Mohamed, Nor Sabirin (Springer Verlag (Germany), 2018)
The invention of a new biopolymer electrolyte based on carboxymethyl cellulose from Hibiscus cannabinus or kenaf fibre has been accomplished by doping ammonium acetate to the polymer–salt system by a solution cast technique. The optical micrograph of all films indicated that the addition of ionic salt enhances the amorphosity of the films. The conductivity values were determined via impedance spectroscopy. The maximum ionic conductivity in the order of 5.77 × 10−4 S cm−1 has been obtained for 20 wt% ammonium acetate-doped carboxymethyl cellulose biopolymer electrolyte. This proved that the insertion of ionic salt into the biopolymer materials successfully improved the conductivity. The prepared films were ionic conductors since the cationic transference number of the biopolymer electrolyte film was ~ 0.99. Transport studies confirmed that the ionic conductivity was influenced by the ionic mobility and diffusion coefficient.